Effect of using aqueous/alcohol solution during solution doping on the physical and chemical characteristics of pre-sintered silica soot and the resultant native glass species concentration - Sua, Y.M.; Chong, W.Y.; Tan, C.C.; Ahmad, Harith; Adikan, Faisal Rafiq Mahamd (2010)
This paper presents the effect of solution doping on pre-sintered silica soot prepared by flame hydrolysis deposition Additionally the effects of using either an aqueous or alcohol solution on the soot layer and the resultant concentration of native glass species (pre- and post-consolidation) are also discussed Soot consisting native glass species such as SiO2 GeO2 P2O5 and B2O3 was pre-sintered with temperatures ranging from 550 C to 950 C before undergoing solution doping Cross-sectional thickness of the soot layer following solution doping was measured via optical microscopy and subsequently compared with those prior to solution doping Significant variations of GeO2 and P2O5 concentration in the soot layer after solution doping were detected via energy dispersive X-ray analysis It was found that apart from the pre-sintered soot layer integrity during solution doping the type of solution used plays an essential role in ensuring retention of native glass species both prior to and following consolidation Measurements using inductively coupled plasma atomic emission spectroscopy confirmed that significant amounts of GeO2 and P2O5 were lost during the immersion in solution stage of the process (C) 2010 Elsevier B V All rights reserved